2016
DOI: 10.1519/ssc.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Strength Training and Metabolic Conditioning for Female Youth and Adolescent Soccer Players

Abstract: CitationWright, M. (2016) AbstractDespite the rapid growth in women and girls playing soccer evidence based guidelines to inform conditioning for girls are sparse. The majority of research on youth soccer is conducted in males, which may not be transferable to practice in female teams. This paper reflects on the current evidence base and draws upon the authors' experiences to provide guidelines to improve conditioning programs throughout maturation in girls. The article focuses on the integration of neuromusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…In this study players were exposed to strength and conditioning training which included neuromuscular training methods to control and reduce force during deceleration e.g. (1,51). Previous research has reported a positive relationship between long-term exposure to strength training and change-of-direction performance in young male soccer players (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study players were exposed to strength and conditioning training which included neuromuscular training methods to control and reduce force during deceleration e.g. (1,51). Previous research has reported a positive relationship between long-term exposure to strength training and change-of-direction performance in young male soccer players (29).…”
Section: Discussionmentioning
confidence: 99%
“…Training should be supervised by an appropriately qualified professional and a progressive curriculum of activities that include the following are recommended; fundamental movement skills, dynamic stability, proprioception or coordination training, plyometric training (progressing from low to high intensity, single to multiple sets of 6-10 repetitions), speed and agility (34) and strength training (e.g. 2-5 sets of 6 -15 repetitions, progressing from fundamental movements such as; the squat, lunge or push up, to sports specific exercises, or by increasing load or velocity over time) (15,33,51). Specific recommendations for practitioners to prescribe metabolic and neuromuscular training for girls soccer players have been published previously (51).…”
Section: Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such the pedagogical approach to delivery included direct instruction, particularly in the early stages and for strength exercises (squat or lunge). However, the coaching of these sessions was fluent and influenced by the approach outlined by Wright and Lass [ 57 ] for pre-pubescent athletes. This included a number of principles of non-linear pedagogy such as an external focus of attention and student–coach interaction; e.g., “move like a frog” and providing references for progressions and regressions of exercises.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the acknowledged importance of developing physical qualities in female soccer players and the increased professionalism of the women's game, it has previously been reported that compliance to supplementary strength and conditioning training is still a relatively new concept for players and coaches (34). This is supported by a recent statement from the Football Association (FA) who have suggested that elite English female soccer players require more 'athleticism' (1) to compete at the international level.…”
Section: Introductionmentioning
confidence: 99%